কালের নিরন্তর যাত্রা : সাবেক আমলার জীবনস্মৃতি - চৌধুরী, আহমদ মাহমুদুর রাজা (ঢাকা : পালক পাবলিশার্স, 2015)
Autobiographical reminiscences of Āhamada Māhamudura Rājā Caudhurī, bureaucrat from Bangladesh.
Donated By Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: Chowdhury, Ahmad Mahmudur Raza; Bangladesh -- Politics and government; Bangladesh -- Officials and employees -- Biography